1967
DOI: 10.1111/j.1476-5381.1967.tb02112.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Responses of the Isolated Portal Vein of the Rabbit to Electrical Stimulation and to Drugs

Abstract: Transmural electrical stimulation has been used to investigate responses of isolated intestinal smooth muscle preparations to nerve stimulation (Paton, 1955;Day & Vane, 1963;Paton & Vane, 1963;Birmingham & Wilson, 1965;Burnstock, Campbell & Rand, 1966). Paterson (1965) stimulated isolated arterial strips transmurally and showed that the ensuing contractions were probably caused by excitation of post-ganglionic adrenergic neurones in the vessel wall.Isolated venous muscle reacts to drugs (Franklin, 1925;Sutter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
1

Year Published

1970
1970
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 27 publications
8
69
1
Order By: Relevance
“…Sutter (1965) found that the external jugular vein of the rabbit was not contracted by isoprenaline but that low doses (below 10 ,ug/ml) caused relaxation of the anterior mesenteric vein (isoprenaline caused contraction above 10 ug/ ml). Hughes & Vane (1967) have shown that isoprenaline (10 ng/ml-1 jg/ml) relaxes the rabbit isolated portal vein, but Hughes (1967) could not demonstrate that isoprenaline in doses up to 10 jg/ml contracted human isolated saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
“…Sutter (1965) found that the external jugular vein of the rabbit was not contracted by isoprenaline but that low doses (below 10 ,ug/ml) caused relaxation of the anterior mesenteric vein (isoprenaline caused contraction above 10 ug/ ml). Hughes & Vane (1967) have shown that isoprenaline (10 ng/ml-1 jg/ml) relaxes the rabbit isolated portal vein, but Hughes (1967) could not demonstrate that isoprenaline in doses up to 10 jg/ml contracted human isolated saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these are excitatory, as for example those to the urinary bladder (Henderson & Roepke, 1934;Chesher, 1967;Dumsday, 1971;Burnstock, Dumsday & Smythe, 1972) and to segments of the gut in lower vertebrates (Everett, 1968;Carter, 1969;Bartlet & Hassan, 1971; Sneddon, Smythe, Satchell & Burnstock, to be published). Others are inhibitory, for example those to the amphibian and reptile lung (Wood & Burnstock, 1967;Campbell, 1971;Robinson, McLean & Burnstock, 1971;Berger, 1972;Schnizer, Hoang & Brecht, 1968) and parts of the vascular system (Hughes & Vane, 1967, 1970. It is not yet known whether any, some, or all of these nerves are purinergic or whether they release yet further neurotransmitters, although some evidence has been presented that those supplying the toad lung (Robinson et al, 1971), guinea-pig bladder (Dumsday, 1971;Burnstock et al, 1972), toad intestine (Sneddon et al, 1972) and rabbit portal vein (Hughes & Vane, 1967) may release ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Others are inhibitory, for example those to the amphibian and reptile lung (Wood & Burnstock, 1967;Campbell, 1971;Robinson, McLean & Burnstock, 1971;Berger, 1972;Schnizer, Hoang & Brecht, 1968) and parts of the vascular system (Hughes & Vane, 1967, 1970. It is not yet known whether any, some, or all of these nerves are purinergic or whether they release yet further neurotransmitters, although some evidence has been presented that those supplying the toad lung (Robinson et al, 1971), guinea-pig bladder (Dumsday, 1971;Burnstock et al, 1972), toad intestine (Sneddon et al, 1972) and rabbit portal vein (Hughes & Vane, 1967) may release ATP.…”
Section: Introductionmentioning
confidence: 99%
“…In most vessels the net effect is a pronounced vasodilatation, although there are exceptions, for instance, the mesenteric portal vein of several species (Hughes & Vane, 1967;Uematsu et al, 1984). The contraction implies the existence of muscarinic receptors on the smooth muscle cells which subserve an excitatory function.…”
Section: Introductionmentioning
confidence: 99%